Critique and Analysis of The Concept of Soul in Naser Khosrow’s Works - Maryam Kasayi; Rahman Zabihi; Mohammad-Taghi Jahani (تاریخ ادبیات)
The main subject of this descriptive-analytical study is to critique and analyze Naser Khosrow’s views of the concept of Soul and to investigate its origins. In Naser Khosrow’s cosmology, the soul stands on the third level of the creation which emerges from the general intellect. The intellect and the soul comprise the masculine-feminine couple of the spiritual world which is the origin of all its lower levels. The general soul, influenced by the general intellect, creates in the spiritual world fortune, opening and imagination and in the physical world generates the general nature, the form and the matter. Plant and animal souls in the lower levels of the world originate from the general soul. The general soul is incomplete compared to the intellect; although to compensate this deficiency, provides the circumstances for human creation by creating lower levels such as celestial bodies and elements as the ultimate goal of creation. The speaking soul in humankind that is a part of the general soul applies the religious teaching and acquiring knowledge to save itself and help the salvation of the general self. The background and origins of Naser Khosrow’s ideas about the soul, in addition to the Islamic teachings, go back to mythology, Greek religious and philosophical teachings, as well as Gnostic and Neoplatonic ideas.